Comparison of the prevalence and associated factors of hyperactive delirium in advanced cancer patients between inpatient palliative care and palliative home care. (12th December 2020) - Hamano, Jun; Mori, Masanori; Ozawa, Taketoshi; Sasaki, Jun; Kawahara, Masanori; Nakamura, Asumi; Hashimoto, Kotaro; Hisajima, Kazuhiro; Koga, Tomoyuki; Goto, Keiji; Fukumoto, Kazuhiko; Morimoto, Yuri; et al.
Abstract: Background: Hyperactive delirium is known to increase family distress and the burden on health care providers. We compared the prevalence and associated factors of agitated delirium in advanced cancer patients between inpatient palliative care and palliative home care on admission and at 3 days before death. Methods: This was a post hoc exploratory analysis of two multicenter, prospective cohort studies of advanced cancer patients, which were performed at 23 palliative care units (PCUs) between Jan and Dec 2017, and on 45 palliative home care services between July and Dec 2017. Results: In total, 2998 patients were enrolled and 2829 were analyzed in this study: 1883 patients in PCUs and 947 patients in palliative home care. The prevalence of agitated delirium between PCUs and palliative home care was 5.2% (95% CI: 4.2% ‐ 6.3%) vs. 1.4% (0.7% ‐ 2.3%) on admission ( p < 0.001) and 7.6% (6.4% ‐ 8.9%) vs. 5.4% (4.0% ‐ 7.0%) 3 days before death ( p < 0.001). However, multivariate logistic regression analysis revealed that the place of care was not significantly associated with the prevalence of agitated delirium at 3 days before death after adjusting for prognostic factors, physical risk factors, and symptoms. Conclusions: There was no significant difference in the prevalence of agitated delirium at 3 days before death between inpatient palliative care and palliative home care after adjusting for the patient background, prognostic factors, symptoms, and treatment. Abstract : We enrolled 2998 patients in palliative care units and home care. A 169 patients were excluded due to the date of death is unknown. We analyzed 2829 patients: 1882 patients in palliative care units, and 947 patients in home care.